The role of the cardiac lymphatic system in the development and progression of heart failure and novel therapeutic approaches for its management in post-infarction cardiac remodeling - Yu. S. Korneva; R. V. Ukrainets (Кардиоваскулярная терапия и профилактика, 2020)
Cardiac lymphatic vessels play a vital role in maintaining homeostasis in both physiological and pathological conditions, providing outflow of metabolites. It has been shown that myocardial infarction and postinfarction cardiac remodeling is accompanied by the lymphatic remodeling, which entails functional disorders and is of great importance in heart failure pathogenesis. As a result of progressive myocardial edema, hypoxia and fibrosis of the interstitial space increase, aggravating edema. Other pathways of additional myocardial damage and contractility reduction are triggered. Lymphatic efflux is associated with arrhythmias. Experimental models showed the positive effect of exogenous activation of lymphangiogenesis in relation to the prevention and treatment of heart failure, which can be further used to improve treatment regimens. This review discusses cardiac lymphatic remodeling after myocardial infarction, as well as the pathogenesis of related complications.